Peran Asam Nukleat dalam Proses Sintesis Protein: Analisis Mekanisme DNA, RNA, dan Ribosom dalam Regulasi Genetik - Amelia Putri Az Azahra; Pramesti Listanto; Khotimah Nur Ramadhani; Tyara Avrilyanti Ghea Indriansyah; Latifa Alya Khairunnisa; Liss Dyah Dewi Arini (Pusat Riset dan Inovasi Nasional, 2025)
Nucleic acids play a vital role in the process of protein synthesis, which is the core of genetic regulation in cells. This process involves a complex mechanism of DNA, RNA, and ribosomes working in a coordinated manner. DNA (deoxyribonucleic acid) functions as a genetic blueprint that stores information for protein synthesis. Through the process of transcription, DNA is transcribed into messenger RNA (ribonucleic acid) (mRNA) in the cell nucleus. mRNA carries the genetic code to the cytoplasm, where ribosomes act as translation centers. Ribosomes, together with transfer RNA (tRNA), read the codon sequence on mRNA to determine the sequence of amino acids that will be assembled into polypeptides. This process, called translation, involves complex interactions between mRNA, tRNA, and ribosomes to ensure that the resulting protein is in accordance with genetic instructions. In addition, the role of non-coding RNA, such as microRNA and riboswitches, is also important in regulating gene expression post-transcriptionally. A deep understanding of the mechanisms of DNA, RNA, and ribosomes has opened up great opportunities in biotechnology and medicine, such as gene therapy and RNA-based drug development. Thus, the analysis of the role of nucleic acids becomes an important foundation in the exploration of molecular biology and genetics.